ANALISA PASAR KLINIK X DI KOTA PONTIANAK - Muhammad Ibnu Kahtan; Arif Wicaksono (JURNAL BORNEO AKCAYA, 2023)
Health clinics as first-level health facilities play an important role in health services. The image of the clinic is very influential in the community who will use the services in the clinic. This survey aimed to determine and analyze the image of Clinic X by community in Pontianak used guided-questionnaires related to top of mind, value, awareness, and brand position with convenience sampling method. The survey was conducted during August 2021 in the car-free day area of Ahmad Yani street Pontianak and Kapuas Square Garden Pontianak. A total of 147 respondents took part in the survey. Clinic X occupies top position in top-of-mind clinics in Pontianak City; The value of Clinic X is a friendly and fair service provider; most respondents are aware of the existence of Clinic X; and the main brand position of Klinik X is the 24-hour Clinic at an affordable cost